TEACHER'S VOCATIONAL TRAINING OF CHILDREN EDUCATION: PROSPECTS TO FULLFILL FORMATION AND SUPERVISION PROJECTS - Galdi da Silva, Rosangela Aparecida; Zauhy Garms, Gilza Maria [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
This paper discusses the initial training theme and summarizes a research for the Master Program of Graduate Studies in Education of the Faculty of Science and Technology - UNESP. The objective was to investigate the problem of initial teacher training in Early Childhood Education Course from the Resolution CNE/CP 1/2006. As bibliographic and documentary research with a qualitative approach, it was identified the challenges posed to professional and public policies and also the precariousness of the Education Course. Also, highlighted the contributions of academic research in the state of knowledge about Early Childhood Education. As a result, we have identified training needs and assumptions indicated to illuminate a curriculum discussion regarding the teacher training in early childhood education with prospects for the realization of projects for training and supervision.
Keywords: Early Childhood Education; Public policy; Pedagogy course; Training. Supervision